2017
DOI: 10.3340/jkns.2016.1212.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Global Sagittal Balance in Koreans Adults

Abstract: ObjectvieThe global sagittal postural patterns as characterized by Roussouly classification have been previously described in various ethnicities, there were no studies investigated in Koreans. To analyze the distribution of the global sagittal postural patterns in Korean adults using Roussouly classification, the author prospectively studied.Methods252 asymptomatic Korean adults was recruited. Data was obtained by reviewing the films for each subject. Spinopelvic parameters were measured and sagittal postural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“… 15 , 16 In the literature, it was reported that as PI values increased, LLA also increased to maintain the sagittal balance, and sacrum formed a horizontal position secondary to this increase. 1 In our study, PI and LLA values were found significantly higher in the listhesis group in accordance with the literature.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“… 15 , 16 In the literature, it was reported that as PI values increased, LLA also increased to maintain the sagittal balance, and sacrum formed a horizontal position secondary to this increase. 1 In our study, PI and LLA values were found significantly higher in the listhesis group in accordance with the literature.…”
Section: Discussionsupporting
confidence: 93%
“… 9 In the case of decreased PI values, the pelvis forms a vertical position, while the increase of the PI values causes the pelvis to form a horizontal position, andthe force distribution of the secondary gravity on the vertebra varies regarding this. 1 It is known that the change in this force distribution increases the probability of spondylolysis, and the higher PI values found in the spondylolisthesis group in our study showed parallelism with the literature. Duval-Beaupere et al also suggested that PI is effective in the formation of isthmic spondylolisthesis, and the larger PI and sacral slope could lead spine to shift.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Yang et al 18 did not find any differences in lumbosacral parameters between female and male asymptomatic individuals. Cho 31 reported that no significant differences were detected in LLA and sacral slope between female and male volunteers. These conflicting results may be a result of different measurement methods and ethnicity.…”
Section: Discussionmentioning
confidence: 96%